Healing Spells in Izyum District: Internal Form and Logic of Functioning - Бондаренко, С. К.; Заїка, С. М.; Рудь, О. М. (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The paper considers text, plot, structure and function of healing spells in Izyum district of Kharkiv region. Discursive codes of the spells are distinguished. The author convincingly proves that the outer shape of the plots, represents an example of Indo-European archaic, synthesized with the folk orthodoxy. In the internal form, they are an example of magical thinking, which operates on the basis of participation principle.